Characterisation and modeling of additively-manufactured polymeric hybrid lattice structures for energy absorption. (1st February 2021) - Sun, Z.P.; Guo, Y.B.; Shim, V.P.W.
Highlights: Original lightweight hybrid lattice structures formulated and fabricated by FDM-based 3D printer to achieve favorable energy absorption characteristic. Addressing limitations of conventional octet topology regarding its severely fluctuating post-yield response following a high yield stress. Stable post-yield stress plateau without sacrificing stiffness and strength significantly in proposed hybrid structures validated by both compression experiments and finite element simulations. Incorporating fabrication-angle-dependent strut material properties into simulations identified as essential to correlate with experimental results. Abstract: Lightweight cellular materials and structures are widely used in load-bearing and energy absorption applications, because of favorable mechanical properties such as high compressibility and low relative density. Recent progress in additive manufacturing techniques has enabled specific architectural geometries of unit cells in cellular structures to be tailored for particular needs. Numerous metallic and polymeric cellular lattices comprising different unit cell topologies have been manufactured and examined in terms of their energy absorption performance. In this study, two designs of hybrid three-dimensional cubic lattices which combine the advantages of an octet and a bending-dominated structure were established, and fabricated via the Fused Deposition Modeling technique. To validate the energy absorption capability of these new hybrid lattices, quasi-static uniaxial compression tests were conducted on samples made from Polylactic Acid. Numerical simulations were also performed to facilitate analysis of the deformation modes of the specimens tested in experiments. Tensile tests on solid dog-bone samples printed at various angles with respect to the build plate reveal fabrication-angle-dependent anisotropy. Consequently, material properties that depend on cell strut inclination were incorporated into the simulations. Compared with a conventional octet that possesses a high stiffness but a fluctuating post-yield response, the experimental results show that the new designs are capable of producing a relatively stable post-yield stress plateau without sacrificing stiffness and strength significantly. The present study indicates the potential for further enhancement of the energy absorption performance of lattice structures by tuning their topological architectures appropriately. Graphical abstract: Image, graphical abstract